ETHICS AND CHALLENGES OF APPLYING ARTIFICIAL INTELLIGENCE IN EDUCATION: A LITERATURE REVIEW - Soliha, Imro Atus (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze the ethics and challenges that arise in the application of Artificial Intelligence (AI) technology in the world of education. Using the literature review method, this study identifies various ethical issues, such as data privacy, equal access to technology, and the role of teachers that are threatened by AI, as well as the technical and social challenges faced by educational institutions in integrating these technologies. Ethical theories of utilitarianism, deontology, and social justice are used as a basis for evaluating the impact of the application of AI in education, both from the perspective of maximum benefits to society and moral and justice principles. The results of this study are expected to provide insight for policymakers and education practitioners in developing ethical and inclusive AI implementation strategies, taking into account the need to maintain the quality of education and protect the rights of students and teachers